2017
DOI: 10.18203/2394-6040.ijcmph20174253
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and obeyance of road traffic rules among motorists in Mangaluru suburbs, India

Abstract: Background: Road traffic accident is one amongst the “biggest killers” across the World according to World Health Organization. Though road traffic accidents are both predictable and preventable, it is witnessed that there is an alarming increase in morbidity, mortality and disability owing to road traffic accident which has become a major public health concern in India. Hence this study aims to assess the awareness and obeyance of road traffic rules among commuters in south Mangaluru suburbs. Methods: A cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
2
1
Order By: Relevance
“…This finding is also almost similar to the findings of the study done among adolescent students of a selected Pre-university College in Raichur city (Ranjan et al, 2018), which revealed that more than half (52.8%) of respondents had adequate knowledge on the road safety rules and regulations. The finding is inconsistent with another study conducted among motorists in Mangaluru suburbs (Shetty et al, 2017) which revealed that more than two-thirds (67.2%) had insufficient awareness about road traffic rules. Again, another study conducted in Multan, Pakistan (Riaz and Shahid, 2018) was contradictory to the findings of the researcher which revealed that the maximum number of professional drivers had inadequate knowledge about traffic sign boards (87.64%) and were less aware.…”
Section: Discussioncontrasting
confidence: 87%
“…This finding is also almost similar to the findings of the study done among adolescent students of a selected Pre-university College in Raichur city (Ranjan et al, 2018), which revealed that more than half (52.8%) of respondents had adequate knowledge on the road safety rules and regulations. The finding is inconsistent with another study conducted among motorists in Mangaluru suburbs (Shetty et al, 2017) which revealed that more than two-thirds (67.2%) had insufficient awareness about road traffic rules. Again, another study conducted in Multan, Pakistan (Riaz and Shahid, 2018) was contradictory to the findings of the researcher which revealed that the maximum number of professional drivers had inadequate knowledge about traffic sign boards (87.64%) and were less aware.…”
Section: Discussioncontrasting
confidence: 87%
“…Nonetheless, since there were little effort in demonstrating of a relationship pertaining to motorists attitude and behaviour in parking legally which will benefit the on-street parking environment in term of economic development and quality of life (Redman, Friman, Gärling, & Hartig, 2013) therefore, it is a worthy effort to carry out a study on relationship on motorists behavioural intention, awareness of the law, the concern of safety and security, parking places and violation, unpaid parking fees and the effectiveness of the enforcement effort in this long outstanding on-street parking issues that enable stakeholders to understand and address it effectively. According to Shetty, D'mello, Purushothama, Rent, and Monisha (2017) more than 67 percent respondents in their research had low awareness about road traffic rules while more than 86 percent of the respondents were not obeying the traffic rules and this has contributed significantly by the ignorance, attitude and behaviourism of motorists. Sani, Tabibi, Fadardi, and Stavrinos (2017) highlighted that motorist with emotional dysregulation was significantly related to driving violations whereas difficulty in regulating emotions was related to driving errors.…”
Section: Introductionmentioning
confidence: 94%
“…Likewise, as in some studies, implementation of effective enforcement has helped in increasing driver compliance (Alsaad, 2021) found that law enforcement does mediate the association between e-government and corruption. However, with the alarming high percentage of respondents with low awareness and disobeying the law (Shetty et al, 2017) and the lack of past studies to investigate these complex issues warrants the need to explore the possibility of how enforcement can be applied to reduce bad motorist behaviour and increase the level of compliance among motorist. Hence, the current study attempted to fill the gaps by examining the role of enforcement as a mediator in the relationship between motorist behaviour and the intention to park legally and between safety and security and the intention to park legally among motorists in the Kuala Lumpur.…”
Section: Introductionmentioning
confidence: 99%